Efficacy and Safety of Vaccination Against Hepatitis B Virus Without Prior Screening Test - Akther, Rabeya; Hossain, Mohammad Zaid; Rabbani, Safia Binte; Hossain, Syeda Fahmida; Chakraborty, Ashim; Biswas, Prodip Kumar (Journal of Dhaka Medical College, 2017)
Hepatitis B virus infection is a major global health problem. There is no specific treatment for acute hepatitis B infection. A safe and effective vaccine, which has been available for more than 30 years, is 95% effective in preventing the development of chronic infection. The employee of Bangladesh Bank and their family member had received 4 doses of Engirex B according to schedule 0, 1,6,12 months without any prior screening test. They received 4th booster dose in 2009.The goal of this study to find out and compare the efficacy and safety of vaccination against HBV without prior screening test. The employee (more than 50years old) underwent annul health check up and their serum HBsAg and Anti-HBs (quantative) were measured in the Immunology department of Bangladesh Institute of Research & Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) and Popular diagnostic center. HBsAg is measured by MEIA method. Anti-HBs (quantative) are measured by chemiluminescence EIA method. 491 subjects have been studied. Among them 480(97.76%) are HBsAg negative and 11(2.24%) cases are HBsAg positive. Ten out of eleven HBsAg positive cases are male. The average anti- HBs titer of the employee is 610.9958(0- >2000 m IU/ml). The average anti-HBs titer of female (n=90) employee is 713(10- >2000 mIU/ml) and average anti-HBs titer of male (n=390) employee is 587.77(0 - >2000 m IU/ml). Female employee developed higher immunity (73.33%) than male employee (56.41%). So it is presumptive that vaccine is safe and effective and we can continue vaccination without prior screening test. J Dhaka Medical College, Vol. 25, No.1, April, 2016, Page 16-25